2016
DOI: 10.1123/ijspp.2015-0686
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of High-Intensity Actions and Physical Performance During a Simulated Brazilian Jiu-Jitsu Competition With a Moderate Dose of Caffeine

Abstract: Caffeine might be an effective ergogenic aid for improving intensity and physical performance during successive elite BJJ combats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 0 publications
0
71
1
2
Order By: Relevance
“…The caffeine doses tested in the trials were 3 mg/kg [55, 56], 4 mg/kg [57], 5 mg/kg [5860] and 6 mg/kg [6, 61, 62]. Supplements were ingested at different times before exercise testing: 30 min [58], 50 min [60] or 60 min [6, 5557, 59, 61, 62]. In one study, the effects of both caffeine and caffeine plus sodium bicarbonate were examined [6].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The caffeine doses tested in the trials were 3 mg/kg [55, 56], 4 mg/kg [57], 5 mg/kg [5860] and 6 mg/kg [6, 61, 62]. Supplements were ingested at different times before exercise testing: 30 min [58], 50 min [60] or 60 min [6, 5557, 59, 61, 62]. In one study, the effects of both caffeine and caffeine plus sodium bicarbonate were examined [6].…”
Section: Resultsmentioning
confidence: 99%
“…Díaz-Lara et al [56] analyzed the effect of caffeine supplementation using a battery of tests designed to assess variables related to taekwondo performance. Astley et al [57] used a specific judo performance test, or special judo fitness test (SJFT), while others assessed performance in a set of 3 repetitions of a specific test such as SJFT [6, 62] or rounds of 1 taekwondo combat [59] or 2 jiu-jitsu combats [55]. Aedma et al [63] simulated a combat-type effort on an arm ergometer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elite athletes typically use different nutritional and ergogenic strategies to improve sport-specific performance, and caffeine is one of the most consumed substances because of its effectiveness to increase physical performance in both team and individual sports [ 1 , 2 , 3 ]. In fact, data obtained from urine samples used to detect doping have revealed that three out of four elite athletes use this substance before or during competition [ 4 ].…”
Section: Introductionmentioning
confidence: 99%